Tratamento de lixiviado de aterro por ozonização fotocatalítica com TiO2 - Carard, Rafael Faria (2018)
This work aims to identify the best treatment condition for an advanced oxidative process of photocatalytic ozonation with titanium dioxide (TiO2) applied to the remediation of the leachate produced at the municipal landfill of Campo Mourão, Paraná. The leachate presents as a complex effluent, with the presence of recalcitrant material, of difficult degradation. Its treatment is considered primordial due to the impacts it causes to the environment and to human health. Considering that the treatments currently employed (biological and physico-chemical) show difficulties in its remediation and may not guarantee a safe disposal in the environment, the application of advanced oxidative processes (AOPs) has become a viable alternative. These methods are based on the generation of hydroxyl radicals (•OH) and other oxidative molecules, from which degrade the pollutants and can carry to their total mineralization in CO2, H2O and inorganic ions. Among the known AOPs, the processes of heterogeneous photocatalysis and ozonation have become common in studies involving leachate. The reconciliation of these processes origins the so-called photocatalytic ozonation, resulting from a strong synergism, which can intensify the degradation of the pollutants, allowing better results, not observed for the processes applied individually. To understand this AOP, the landfill leachate treatment was carried out using a photocatalytic chamber and an ozonation system based on the corona effect. The monitoring parameters of pH, temperature, turbidity, apparent color, true color, filtrate chemical oxygen demand (COD-F), biochemical oxygen demand (BOD520), ammoniacal nitrogen (NH4-N), nitrite (NO2--N) and nitrate (NO3--N) were measured. A statistical design of the central composite rotable design (CCRD) model was elaborated to the data and to define the optimum condition for removal of COD-F (%) and increase of the biodegradability (BOD/COD) of the effluent, being observed the removal and behavior of the other parameters. The characterization of the leachate allowed to define that it is in the transition phase to stabilized methanogenic. The statistical model obtained was valid for the data of reduction of COD-F (%) and increase of biodegradability in the effluent, with R² equivalent to 0,88 and 0,89 and R-adjusted equivalent to 0,80 and 0,84, respectively, characterizing high values, allowing to define the optimum operating condition of the system regarding these parameters. The pH was reduced, the temperature remained within a suitable range and the turbidity increased in all treatment assays. The removal of apparent color was varied, reaching a maximum of approximately 64% and for true color was higher than 70%, in most assays. The maximum COD-F (%) reduction was approximately 30% and of NH4-N corresponded to approximately 90%, in the best condition previously established by the CCRD. The treatment did not allow to reach the permissible limits for disposal of the effluent in the environment, according to the Brazilian environmental legislation. The noticeable increase in biodegradability (BOD/COD) in the leachate suggests that the UV/TiO2/O3 process should be used as a complementary treatment with physico-chemical or preferably biological post-treatment.